TNFAIP3 F127C Coding Variation in Greek Primary Sjogren’s Syndrome Patients - Adrianos Nezos; Eliona Gkioka; Michael Koutsilieris; Michael Voulgarelis; Athanasios G. Tzioufas; Clio P. Mavragani (Journal of Immunology Research)
Tumor necrosis factor, alpha-induced protein 3 (TNFAIP3) gene encodes the A20 protein, an important negative feedback regulator of the nuclear factor kappa-light-chain-enhancer of activated B cell (NF-κB) pathway. A coding TNFAIP3 variant, namely rs2230926, has been previously linked to B cell non-Hodgkin’s lymphoma (NHL) development in patients with Sjogren’s syndrome (SS) of French and UK origin. Herein, we aimed to determine the prevalence of rs2230926 in a Greek primary SS cohort and explore possible associations with disease characteristics. The rs2230926 gene variant was genotyped in 327 primary Greek SS patients (ninety-one complicated by NHL (SS-lymphoma)) and 448 Greek healthy controls (HC) of similar age and sex distribution. Clinical and laboratory characteristics were also recorded and gene expression of relevant genes of the NF-κB pathway was quantitated by real-time PCR in available whole peripheral blood (PB) from 165 primary SS patients. Increased prevalence of the rs2230926 mutant variant was detected in both SS-lymphoma and SS-nonlymphoma subgroups compared to HC (8.8% vs. 7.6% vs. 3.6%, p values: 0.04 and 0.03, respectively) in association with higher IgM, LDH serum levels, and PB Bcl-XL transcripts but lower leucocyte and neutrophil counts. Of interest, approximately one-fifth of SS-lymphoma cases with age at disease onset ≤ 40 years carried the rs2230926 variant (18.2% vs. 3.6%, OR 95% (CI): 6.0 (1.8–19.8), p value: 0.01). We postulate that deregulation of the NF-κB pathway as a result of the TNFAIP3 rs2230926 aberration increases SS and SS lymphoma susceptibility particularly in patients with early disease onset.